A new species of Coryphophylax Fitzinger in: Steindachner, 1867 (Sauria: Iguania : Agamidae) from the Andaman Islands, India - Harikrishnan, S.; Vasudevan, K.; Chandramouli, S.R.; Choudhury, B.C; Dutta, S.; Das, I. (Zootaxa, 2012)
The systematic position of the agamid genus Corphophylax (Squamata Agamidae) is given as monotypic and endemic to the Andaman and Nicobar Islands in the Bay of Bengal, India.